Someone saw something (Mira, 2024)
When six-year-old Gabriel vanishes from Central Park, his mother, news anchor Corina Corado, is desperate for answers. Who would take her son--and why? Detectives suspect there's a connection to the barrage of hate mail Corina's received over the years. In her line of work, it's not unusual for agitated conspiracy theorists to send messages that threaten violence...or worse. But as the investigation deepens, the secrets that Corina, her husband, Robert, and her stepdaughter, Charlotte, have kept start to unravel. As the truth behind Gabriel's disappearance emerges, Corina must race the clock to track down her missing child...before paying the ultimate price.

Table for two: fictions (Viking, Books on Tape, Penguin Publishing Group, 2024)
"The millions of readers of Amor Towles are in for a treat as he shares some of his shorter fiction: six stories set in New York City and a novella in Los Angeles. The New York stories, most of which are set around the turn of the millennium, take up everything from the death-defying acrobatics of the male ego, to the fateful consequences of brief encounters, and the delicate mechanics of comprise which operate at the heart of modern marriages. In Towles's novel, Rules of Civility, the indomitable Evelyn Ross leaves New York City in September, 1938, with the intention of returning home to Indiana. But as her train pulls into Chicago, where her parents are waiting, she instead extends her ticket to Los Angeles. Told from seven points of view, "Eve in Hollywood" describes how Eve crafts a new future for herself-and others-in the midst of Hollywood's golden age. Throughout the stories, two characters often find themselves sitting across a table for two where the direction of their futures may hinge upon what they say to each other next. Written with his signature wit, humor, and sophistication, Table for Two is another glittering addition to Towles's canon of stylish and transporting historical fiction"--

Holmes, Marple & Poe (Holmes, ,, 2024)
"In New York City, three intriguing, smart, and stylish private investigators open Holmes, Marple & Poe Investigations. Who are these detectives with famous names and mysterious, untraceable pasts? Brendan Holmes--The Brain: Identifies suspects via deduction and logic. Margaret Marple--The Eyes: Possesses powers of observation too often underestimated. Auguste Poe--The Muscle: Chases down every lead no matter how dangerous or dark. The agency's daring methodology and headline-making solves attract the attention of NYPD Detective Helene Grey. Her solo investigation into her three unknowable competitors rivals the best mysteries of Sir Arthur Conan-Doyle, Agatha Christie, and Edgar Allan Poe"--

The book of doors: a novel (HarperCollins, HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, 2024)
When her favorite customer, a lonely yet charming old man, dies right in front of her, Cassie holds on to the last book he was reading, which turns out to be a rare volume that has great power and she is tasked with protecting it from those who will do evil.

Trust (Riverhead Books, 2022)
"An award-winning writer of absorbing, sophisticated fiction delivers a stylish and propulsive novel rooted in early 20th century New York, about wealth and talent, trust and intimacy, truth and perception. In glamorous 1920s New York City, two characters of sophisticated taste come together. One is a legendary Wall Street tycoon; the other, the brilliant daughter of penniless aristocrats. Steeped in affluence and grandeur, their marriage excites gossip and allows a continued ascent--all at a moment when the country is undergoing a great transformation. This is the story at the center of Harold Vanner's novel Bonds, which everyone in 1938 New York seems to have read. But it isn't the only version. Provocative, propulsive, and repeatedly surprising, Hernan Diaz's TRUST puts the story of these characters into conversation with the "the truth"--and in tension with the life and perspective of an outsider immersed in the mystery of a competing account. The result is an overarching novel that becomes more exhilarating and profound with each new layer and revelation, engaging the reader in a treasure hunt for the truth that confronts the reality-warping gravitational pull of money, and how power often manipulates facts."--
Bonds / Harold Vanner --, My life / Andrew Bevel --, A memoir, remembered / Ida Partenza --, Futures / Mildred Bevel.